Law and the hospitality industry - Towers-Romero, Sandi (Carolina Academic Press, 2024)
"Law and the Hospitality Industry offers students an affordable and concise introduction to hospitality law. Starting with an overview of hospitality areas (travel agents, transportation, lodging, food services, tour operators and attractions/entertainment), the text explores the intersection of law and topics such as business structures, contracts, torts, property, employment, IP, safety, insurance and ethics. Chapter summaries, key terms, discussion questions and bibliographies, help students absorb concepts. The second edition includes updates to employee rights, compensation, ACA benefits, and affirmative action. Also, new content on the expanding role of hospitality associations has been added. This edition explores the impact of the latest state regulations and federal laws on the industry. Finally, updated case materials provide insight into the changing legal landscape of hospitality"--
includes references and index
Keywords: Hotels -- Law and legislation; Hospitality industry -- Law and legislation; Hotel management -- Law and legislation; Tourism -- Law and legislation